PENGARUH OPTIMASI MEDIA SOSIAL TERHADAP EFEKTIVITAS PEMASARAN DIGITAL PADA USAHA RITEL TRUSTMART (Studi pada Usaha Ritel Trustmart di Kabupaten Pesawaran) - Prikurnia, Anas Khair; Octavini, Nanda Andreas; Sari, Rika Purnama (Journal of Economic and Business Retail, 2021)
ABSTRACTThe purpose of this study was to determine the effect of sicial networks and websites on the effectiveness of digital marketingin the Trustmart retail business in Pesawaran Lampung . The sample in this study were selected using purposive sampling and consists of consumers who had purchased products at Trustmart. The research data analysis using multiple regression techniques to test equipment SPSS 16. Results of this study indicate that the effectiveness of digital marketing in the Trustmart retail business is in influenced by promotional factors througt social networks and websites. The F test showed simultaneous social networks and websites on has a positive and significant influence on the image of effectiveness digital markerting.